PERILAKU PETANI SALAK PASCA PENETAPAN DESA TANJUNGHARJO SEBAGAI AGROWISATA SALAK BOJONEGORO - Moch Suberi (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2016)
Bojonegoro District Government has been choose Tanjungharjo village as a agrotourism village with the main aims are to proverty alevation and increasing this society income. This research conducted to alayze the behavior of Salak Farmes before and after the implementation of agrotourism “Kampung Salak” at Tanjungharjo village. The aim for this research is to explore the behavior of salak farmers before and after the establishment of Tanjungharjo Village as an Agro-tourism Village.